PERSEPSI KARYAWAN TENTANG PERAN MOTIVASI DAN KEPUASAN KERJA DALAM MENINGKATKAN RETENSI KARYAWAN DI PT. INDO TIMUR PRIMA - Nasir, Nasir (Jurnal Manajemen dan Pemasaran, 2025)
Employee retention is one of the main challenges in human resource management, especially in competitive industries such as PT. Indo Timur Prima. Job motivation and job satisfaction are considered important factors that influence an employee's decision to stay in the company. This study aims to analyze employee perception of the role of job motivation and job satisfaction in increasing employee retention at PT. Indo Timur Prima. This study uses a qualitative approach with a case study method. The data was collected through in-depth interviews with 10 informants consisting of employees with more than two years of service. Data analysis was carried out with thematic techniques to identify the main patterns and themes that emerged from the interviews. The results of the study show that high work motivation, both intrinsic and extrinsic, significantly influences employees' decision to persevere. In addition, job satisfaction influenced by relationships between colleagues, recognition of achievements, and a conducive work environment are also the main factors in employee retention. However, some challenges such as excessive workload and limited career development opportunities were found to reduce job satisfaction. In conclusion, work motivation and job satisfaction have a very important role in employee retention at PT. Indo Timur Prima. Companies are advised to improve their employee development strategies and create a supportive work environment to strengthen employee loyalty.